Winners’ strategies: Comprehensive analysis and optimization of 2-point shots in 3x3 basketball using multi-criteria decision support analysis, on the example of two Olympic National Teams - Michał Nowak; Michał Skalik; Jakub Więckowski; Radosław Ciejpa; Artur Stolarczyk; Łukasz Oleksy (PLoS ONE, 2025)
The study presents an innovative approach to analyzing and optimizing 2-point shooting strategies in 3x3 basketball, using newly defined parameters and multi-criteria decision analysis (MCDA). A comparative analysis of the results of the Polish and Serbian national teams from the Olympic Games in Tokyo 2020 allowed us to identify key factors influencing the effectiveness of shots, such as the location of the shot, interaction with the defender, and the time of the action. It was shown that the Serbian team was more effective, which translated into a better result. Differences in shooting strategies were identified, especially in the crucial second half of the match, emphasizing the importance of tactical flexibility. Multi-criteria modeling showed that two factors – the effectiveness of shots and the average duration of an action – could be used to optimize game strategy. To leverage these findings, we emphasize the need for individualized training measures focused on generating shooting opportunities for oneself and teammates, which in turn increases decision-making effectiveness in key moments (e.g., when trailing in score). 3x3 basketball offers a unique opportunity to analyze strategies that rely more on cooperation, creativity, and improvisation than on the strictly defined tactical systems of 5x5. Research into this format can contribute to a deeper understanding of decision-making processes, shooting efficiency, and adaptive responses of players in high-intensity situations, which may also apply to other fast-paced team sports. This study proposes to continue the research with larger numbers of teams to develop new models for a more detailed understanding of shooting efficiency in this discipline, including the influence of fatigue, tactical adjustments, and partial automation of measurements. These further studies will fill existing research gaps and positively impact the development of this new Olympic discipline. This is one of the first studies to apply multi-criteria decision analysis to 3x3 basketball tactics.